50. Evaluation of Discordant Results Between Filmarray Meningitis/encephalitis Panel and Conventional Testing in Pediatric Patients: A Multi-site Retrospective Cohort Study. (31st December 2020) - Ekambaram, Maheswari; Nabower, Aleisha M; Ampofo, Krow; Gollehon, Nathan S; Goodrich, Nathaniel; Martin, Kimberly C; McCulloh, Russell; Rajbhandari, Prabi; Snowden, Jessica
Abstract: Background: FilmArray Meningitis/Encephalitis Panel (ME panel) has a 11% false positive and 2.2% false negative rate compared to conventional testing. We aim to describe characteristics, treatment decisions and outcomes in pediatric patients with discordant results between ME panel and conventional testing. Methods: We conducted a multisite (n=4) retrospective review of patients < 18 years with positive cerebrospinal fluid (CSF) results by ME panel or conventional testing (CSF culture, Herpes Simplex Virus [HSV] and enterovirus [EV] PCR) from time of local ME panel implementation to February 2019. We excluded CSF obtained for non-infectious reasons. Demographic and clinical data were extracted from electronic medical records. Comparison between concordant and discordant results were made using Mann-Whitney test for continuous and Fisher's exact test for categorical variables. Results: A total of 355 patients had at least 1 positive result. Baseline characteristics and pathogens are shown in Table 1 and 2. Of the 53 bacterial pathogens identifiable by ME panel, 31 (58%) had discordant results – 29 positive by ME panel only and 2 by culture only (both E.coli ). Patients with bacterial pathogens identified by ME panel only had lower CSF WBC and protein but higher CSF glucose (Table 3). Five patients with bacteria identified on ME panel only were not treated as meningitis given lack of pleocytosis, no antibiotic pretreatment and negative repeat cultures. Of these, 4 recovered without complications but one had hypoxic encephalopathy. Two patients had HSV noted in ME panel but individual PCR negative. The first was a 13-day-old with typical skin lesions and positive surface swab. The other was a 6-day old only with CSF pleocytosis. Both had abnormal neuroimaging and were treated as true cases. Of 24 who had both EV PCR and ME panel, 7 were positive by ME panel only and 3 by PCR only. Table 1: Baseline Characteristics of the Study Population Table 2: Pathogens identified via CSF Culture, ME panel or Conventional PCR Table 3: Characteristics of Discordant Results for Bacterial Pathogens Tested in ME panel Conclusion: More than half of bacterial pathogens identified by ME panel did not have a corresponding positive CSF culture. No difference was noted by antibiotic pretreatment. Treatment decisions based on positive ME panel should be made in the appropriate clinical context. Likewise, a negative ME panel does not rule out infection especially when atypical organisms are suspected. Disclosures: Krow Ampofo, MBChB, Merck (Grant/Research Support)